PERTARUNGAN WACANA PEMERINTAH DAN PUBLIK TENTANG PANDEMI COVID-19 - Nursatyo Nursatyo; Humaini Humaini (Jurnal Penelitian Sosial Ilmu Komunikasi, 2021)
The Covid-19 pandemic around the world has caused various problems, especially in the health and economic sectors. Various efforts have been made by the government to overcome the impact of Covid-19. One of the government's efforts is to carry out various public communication strategies to influence public discourse and behavior in order to avoid the virus. However, the government's efforts to construct public discourse must deal with other discourses that are sourced from information spread on the internet. This article seeks to understand the construction of government discourse and other discourses by using secondary data from internet. The conclusion that can be drawn is that the discourse constructed by the government in an effort to deal with the impact of the Covid-19 pandemic is that there is always a middle way between health interests and economic interests. People must remain productive at work while maintaining health. Meanwhile, another public discourse that has also developed is that Covid-19 is a form of global conspiracy that aims to destabilize the world economy.